2020
DOI: 10.1186/s12915-020-00797-1
|View full text |Cite
|
Sign up to set email alerts
|

The roles of hybridization and habitat fragmentation in the evolution of Brazil’s enigmatic longwing butterflies, Heliconius nattereri and H. hermathena

Abstract: Background: Heliconius butterflies are widely distributed across the Neotropics and have evolved a stunning array of wing color patterns that mediate Müllerian mimicry and mating behavior. Their rapid radiation has been strongly influenced by hybridization, which has created new species and allowed sharing of color patterning alleles between mimetic species pairs. While these processes have frequently been observed in widespread species with contiguous distributions, many Heliconius species inhabit patchy or r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 104 publications
4
16
0
Order By: Relevance
“…15-kb, typical of Heliconius ) for all 16 species, including part of the mitochondrial DNA control region. A genealogy based on these mitochondrial genomes (Figure 1A) did not differ from that for the mitochondrial genomes assembled using reference-aided approaches (Kozak et al 2015; Massardo et al 2020), thereby validating our de novo approach.…”
Section: Resultssupporting
confidence: 60%
“…15-kb, typical of Heliconius ) for all 16 species, including part of the mitochondrial DNA control region. A genealogy based on these mitochondrial genomes (Figure 1A) did not differ from that for the mitochondrial genomes assembled using reference-aided approaches (Kozak et al 2015; Massardo et al 2020), thereby validating our de novo approach.…”
Section: Resultssupporting
confidence: 60%
“…The de novo assembly of Heliconius mitochondrial genomes enables the recovery of near-complete mitochondrial sequences (∼15 kb, typical of Heliconius— see, e.g., Massardo et al 2020 ) for all 16 species, including part of the mitochondrial DNA control region. A genealogy based on these mitochondrial genomes ( fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the range of H. hecalesia does overlap with that of H. clysonymus and its sister species H. hortense in West Ecuador, the Colombian Andes, and Central America (Rosser et al 2012), and there are documented natural hybrids between H. hecalesia and both H. clysonymus and H. hortense (Mallet et al 2007). Previous phylogenetic studies showed that H. telesiphe forms a well-supported clade with H. clysonymus and H. hortense, nested within the erato clade (Kozak et al 2015;Massardo et al 2020). Therefore, it is likely that the signal from introgression loci in H. hecalesia might come from H. clysonymus, H. hortense, or any ancestral population of these three species.…”
Section: Evidence Of Introgression In the Wildmentioning
confidence: 99%
“…In this case, it did not seem to produce reliable inference of the species tree and introgression events, with considerable uncertainty surrounding the tree topology and the timing and direction of introgression events. Finally, Massardo et al (2020) analyzed the genome data from Edelman et al (2019) together with three additional genomes in both erato-sara and melpomene -silvaniform clades and inferred species trees using the same approach as in Edelman et al (2019).…”
Section: Introductionmentioning
confidence: 99%